Environmental Crisis: A Global Threat of Human Security - Winarno, Budi (Jurnal Hubungan Internasional, 2017)
Global warming and climate change  are not more than  an environmental crisis in the era of  neoliberal globalization. This has been a global issue, and in the same time, it has been gradually becoming a global threat of human security.  Global awareness among leaders of the countries in the world,  and among international communites, are needed to stand together in order to strenghening regional organization and international regime solving this threat of environmental crisis. A global awareness and cooperation among emerging and developed countries are needed  to rise their polical will substantially,  and  most important is  to rule out polical economy interest of the developed countries in order to  bring about regional organizations  and  international regime of global environment having more capacity to solve environmental crisis